Professor M. А. Kravchenko – organizer of experimental work in animal husbandry of Ukrainian SSR - Schulha, V. P. (History of science and technology, 2017)
Contribution of Doctor of Agricultural Sciences, Professor M. Kravchenko in the formation of Department of Cattle Industry of Kyiv Experimental Livestock Station "Terezine" and Department of Breeding Work of Central Research Station of Farm Animal Artificial Insemination (Brovary) was highlighted. His research developments on breeding improving of Simmental, Black-and-White and White-Headed Ukrainian breeds of cattle, which were the most widespread in their service area were summarized. The effectiveness of breed improvement actions proposed by M. Kravchenko to increase the profitability of the domestic cattle industry in the Ukrainian SSR of 50-80-s of the XX century was proven.